Technological culture and the ecosystem: A proactive global community towards environmental protection and development - Estonilo, Amado Galo J., III (Animo Repository, 2011)
This paper will identify and explain the ecological crisis and the problems that humanity is experiencing today. It will also emphasize what and how technological culture affect the integrity of the environment. Moreover, the paper will offer various means and paradigms to preserve and conserve our environment, there are concrete projects and activities which are available for everyone to learn and replicate in their homes and communities. Two landmark environmental documents will be given prominence in this paper: first, the1988 pastoral letter of the Catholic Bishops Conference of the Philippines, “What is happening to our beautiful land”; and second, Republic Act no. 8749, or more popularly known as, “The Philippine Clean Air Act of 1999.”